Investor trading behavior: empirical evidence from the Egyptian stock exchange - Khalil, Heba Mohamed (AUC Knowledge Fountain, 2015)
Using unique, intraday transactions data from Egypt, this study examines the extent to which past returns, over several intervals going back to up to six months of past returns, and the level of sophistication of the different investor types, determine the propensity of different investor groups to buy and sell. I adopted the buy ratio differences method to determine which investors adopt a momentum behavior and which investors adopt a contrarian behavior. I find that non-Arab foreign investors tend to be momentum investors, buying past winning stocks and selling past losers while domestic investors, especially individual investors, tend to exhibit contrarianism. The distinctions in behavior are, to a great extent, consistent across the five different past-return intervals.